경안천 용존 산소 예측을 위한 입력 인자 선정 및 기계 학습 모델 비교 - 김민지(Min Ji Kim); 변선정(Seon Jeong Byeon); 김경민(Kyung Min Kim); 안종화(Johng-Hwa Ahn) (Daehan hwan'gyeong gonghag hoeji, 2021)
목적:본 연구에서는 경안천의 용존 산소(dissolved oxygen, DO) 예측을 위해 기계 학습(machine learning) 모델의 최적 입력 인자를 선정하고 성능 평가 지표 결과를 비교하여 최적 모델을 찾고자 한다. 방법:경안천 특정 지점의 수질 자료를 연구대상으로 삼아 1998년 1월 15일부터 2019년 12월 30일까지 자료를 수집하고, 전처리한 데이터를 7:3의 비율에 따라 train과 test 자료로 나누어 실험을 진행하였다. 기계 학습 중 랜덤 포레스트(random forest, RF), 인공신경망(artificial neural network, ANN), 합성곱 신경망(convolutional neural network, CNN), 게이트 순환 유닛(gated recurrent unit, GRU) 등을 이용하였다. RF와 ANN은 무작위 추출(random split)과 시계열 자료(time series)로 구분하여 실험하였으며, CNN과 GRU는 시계열 자료만 이용하여 실험을 진행하였다. 모델별 최적의 결과를 비교하기 위해 성능 평가 지표(결정 계수(square of the correlation coefficient, R2), 평균 제곱근 오차(root mean square error, RMSE), 평균 절대 오차(mean absolute error, MAE))를 사용하였다. 결과 및 토의:RF 기여도 분석 결과와 참고문헌을 통해 최적 입력 인자로 수온, pH, 전기 전도도, PO4-P, NH4-N, 총 인, 부유물질, NO3-N 등으로 선정하였다. RF와 ANN 모두 무작위 추출보다 시계열 자료의 성능이 더 우수하였다. 시계열 자료를 이용하여 모델 성능을 비교해 보면, RF > CNN > GRU > ANN 순으로 나타났다. 결론:본 연구에서 경안천의 DO 예측을 위한 기계 학습 모델의 최적 입력 인자로 8개(수온, pH, 전기 전도도, PO4-P, NH4-N, 총 인, 부유물질, NO3-N)를 선택하였다. DO 예측에 가장 우수한 모델은 시계열 자료를 사용한 RF 모델이었다. 따라서 경안천과 같은 하천의 DO를 예측하는 경우 최적 입력 인자 선정 후 시계열 자료를 바탕으로 RF 모델을 이용할 것을 제안한다. Objectives:In this study, we select input factors for machine learning models to predict dissolved oxygen (DO) in Gyeongan Stream and compare results of performance evaluation indicators to find the optimal model. Methods:The water quality data from the specific points of Gyeongan Stream were collected between January 15, 1998 and December 30, 2019. The pretreatment data were divided into train and test data with the ratio of 7:3. We used random forest (RF), artificial neural network (ANN), convolutional neural network (CNN), and gated recurrent unit (GRU) among machine learning. RF and ANN were tested by both random split and time series data, while CNN and GRU conducted the experiment using only time series data. Performance evaluation indicators such as square of the correlation coefficient (R2), root mean square error (RMSE), and mean absolute error (MAE) were used to compare the optimal results for the models. Results and Discussion:Based on the RF variable importance results and references, water temperature, pH, electrical conductivity, PO4-P, NH4-N, total phosphorus, suspended solids, and NO3-N were used as input factors. Both RF and ANN performed better with time series data than random split. The model performance was good in order of RF > CNN > GRU > ANN. Conclusions:The eight input factors (water temperature, pH, electrical conductivity, PO4-P, NH4-N, total phosphorus, suspended solids, and NO3-N) were selected for machine learning models to predict DO in Gyeongan Stream. The best model for DO prediction was the RF model with time series data. Therefore, we suggest that the RF with the eight input factors could be used to predict the DO in streams. KCI Citation Count: 1